Full Scale Dent Rebound Testing of X65 Steel Linepipe. Issue 3 (January 2021) - Sha, Shengyi; Jia, Guangming; Yan, Bingchuan; Chen, Pengchao; Pang, Shengmin; Feng, Qingshan
Abstract: Dents in buried pipelines can be formed due to a number of causes: third party machinery strikes, rock strikes during backfilling, pipe resting on rock, and amongst others. Dents in pipelines would not only affect short and/or long-term integrity, but would also have a potential impact on the pass capacity of in-line inspection and cleaning tools when the size of the dent is large enough. Rebound for an originally constrained dent can decrease the dent depth and improve the pass capacity of in-line inspection and cleaning tools. In order to estimate the rebound capacity of dents especially in spiral weld pipelines, a full-scale dent rebound testing program of X65 steel pipeline was designed and performed. The full scale testing was conducted on the parent material and the spiral welds. Hemispherical and pyramidal indenters were used to generate dents to different depths. Strains around the denting area during formation of the dent and changes in depths due to rebounding after removing indenter were measured. Following each rebound test, the dent profile was portrayed with a 3D laser scanner and the maximum equivalent strain was then calculated. With the information obtained from the above measurements, detailed analyses were performed and a numerical model was developed. In this paper, the approach used for the study is described first. The results and findings are then presented. The effectiveness of the developed numerical model for dent integrity management is demonstrated.